How important is the study of pragmatics to train students' communication skills in facing the challenges of the 21st century? - Marni, Silvia; Tiawati, Refa Lina; Helda, Trisna; Rahmat, Wahyudi (Journal of Pragmatics and Discourse Research, 2024)
This research aims to analyze pragmatic aspects in Indonesian language textbooks at junior high school (SMP) level. The research method used is qualitative analysis of the texts in the selected textbooks. Data was collected through observation of speech acts in the text, including language use, communicative context, and pragmatic implicatures contained therein. The results of the analysis show that middle school Indonesian language textbooks generally pay attention to pragmatic aspects in selecting and compiling texts, but there are still several shortcomings in their application. Some of these shortcomings include the use of language that is not appropriate to the communicative context, as well as a lack of emphasis on pragmatic aspects which are important in learning Indonesian. The implication of this research is the importance of greater attention to pragmatic aspects in preparing Indonesian language textbooks, to ensure that the texts presented can provide students with a better understanding of language use in various communicative situations.